A GIS-supported 3D approach for flood risk assessment of the Qu'Appelle River, Southern Saskatchewan. (24th April 2006) - Abdalla, Rifaat; Tao, C. Vincent; Wu, Huayi; Maqsood, Imran
This research introduces a hybrid approach for flood risk assessment through GIS. The developed approach is based on the integration of hydraulic simulation and GIS analysis, which allows spatial-based visualisation and prediction of flood disaster. In particular, the Hydraulic Engineering Center River Analysis System (HEC-RAS) model is employed to simulate multi-scenario flood cases within a Canadian context; the dimensional stream channel model is constructed based on geometry obtained from Digital Elevation Model (DEM), and ArcView GIS software is used for producing water surface grids, and Triangular Irregular Network (TIN) model is utilised for the study area based on Digital Terrain Model (DTM). The developed approach is applied to a section of the Qu'Appelle River in southern Saskatchewan. The results indicated that the developed methodology is efficient in modelling and visualising the spatial extent of different flood scenarios and in determining flooded areas at risk. It was found that changes in water elevations of the Qu'Appelle River made the downstream areas more at risk.